Reforms in Higher Education in New Uzbekistan and Their Objectives - Yoqubjonov , Umarali (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the fundamental reforms implemented in the higher education system of Uzbekistan since 2017, the quantitative and qualitative indicators of the system, as well as the strategic goals set until 2026.